Need Analysis of Learning Resources for Teaching Gas Chromatography Materials - Ade Ariyani; Manihar Situmorang; Simson Tarigan (Didaktika: Jurnal Kependidikan, 2024)
The availability of learning resources is an important component in lectures so that students can learn chemistry optimally and maximize their potential. The aim of this research is to describe the results of interviews and questionnaires analyzing learning resource needs by lecturers and students regarding learning gas chromatography in separation chemistry courses at Medan State University. This study used descriptive qualitative method. The respondents were one scholarship chemistry lecturer and 30 Chemistry Department students who had taken separation chemistry courses. This research instrument uses interview sheets and needs analysis questionnaires presented on the Google Form platform. Data analysis techniques by describing data from interviews and questionnaires regarding the need for gas chromatography learning resources are explained in detail. The results of this research are that students need learning resources in the form of open materials and virtual laboratories to support the learning process in separation chemistry subjects, especially gas chromatography. The learning resources in question are project-based learning resources that can be accessed online/digitally, containing gas chromatography teaching materials, equipped with examples of relevant contextual projects, illustrations with virtual laboratory media integration, hyperlinks to trusted websites, problem solving tests and evaluations. able to make students very enthusiastic about working on projects, completing and submitting reports correctly so that they can improve their learning outcomes and skills in gas chromatography material. It is hoped that the results of the analysis can be used as a basis for developing learning resources according to student needs.